Socio-psychological Profile of a Person Who Confidentially Provides Assistance to the Operational Unit - Khalymon, Serhiy; Polovnikov, Vadym; Volynets, Pavlo ([Madrid] : Colegio Oficial de Psicólogos de Madrid, 2020)
The article presents the analysis of the specific socio-psychological characteristics of the people who confidentially assist the operational units of the State Border Guard Service of Ukraine, with the aim of knowing the typical socio-psychological profile of the confidential informant. To this end, a survey was conducted among 84 officers who performed operational and service tasks with these people. The study evaluated the sociodemographic (gender, age, education) and psychological (temperament, reasons for cooperation, nature of the relationships between them and the operational personnel, attitude of the confidential informants towards the tasks) characteristics, and the operational and investigative characteristics (qualities of intelligence, quality of the operational information provided, duration of assistance to the operational unit, etc.). The synthesis and interpretation of the results of the survey gave the possibility to know the socio-psychological profile of the volunteer assistant of the operational unit of the State Border Guard Service of Ukraine, and to compare the individual specific characteristics of the relevant confidential informant with those from other law enforcement agencies in foreign countries who cooperate with Ukraine. It is concluded that the knowledge of the socio-psychological profile of informants by the operational officials is of great importance to provide confidential assistance to the operational units. The differences between the activities of the corruption claimants, whose characteristics were provided by foreign scientists, and of confidential informants, who provide assistance to the operating units, are mainly explained by the fact that informants cooperate in a confidential format (not publicly) and their activities are related to a wider range of issues.
Descripción basada en Anuario de psicología jurídica, vol. 30 (2020), P. 13-20.
Descripción basada en metadatos suministrados por el editor y otras fuentes.
Recurso electrónico. Santa Fe, Arg.: elibro, 2023. Disponible vía World Wide Web. El acceso puede estar limitado para las bibliotecas afiliadas a elibro.
Keywords: Actividad operativa y de investigación.; Denunciantes; Informantes confidenciales; Perfil socio-psicológico.; Unidades operativas; Artículos.